IN-VITRO NUTRITIONAL, PHYTOCHEMICAL, ANTIOXIDANT AND ANTI-INFLAMMATORY ANALYSES INDICATED DISPARITY IN Cola nitida L. and Garcinia kola Heckel USED IN NIGERIA - Apiamu, Augustine; Orhonigbe, I.; Evuen, Uduenevwo F.; Kadiri, Helen E.; Okoro, Israel O.; Kpomah, Enyohwo D. (FUDMA JOURNAL OF SCIENCES, 2023)
The research affirmed that Cola nitida L. and Garcinia kola Heckel used in Nigeria are quite different medicinally and nutritionally. The proportions of all nutrients analyzed quantitatively (lipid, moisture, fibre, ash, and protein except carbohydrate) were greater in C. nitida than in G. kola Heckel (p
Keywords: Anti-inflammatory; Antioxidant; Cola nitida; Garcinia kola Heckel; Phytoconstituents